Analisis Penyebab Keterlambatan Berbicara Pada Anak Usia 3 Tahun Di Rumoh Terapi Tabina - Mulya Riyyana; Jaizaton Muzil; Yeni Susanti; Hijriati Hijriati (Nunchi : Islamic Parenting Journal, 2024)
Speech delays in children are part of the language development aspect. A child can be said to have Speech Delay if his speaking ability is far below the average for children his age. The aim of this research is to determine the causes of speech delays in 3 year old children at the Rumoh Terapi Tabina. The method used in this research is a qualitative description method. The qualitative description method is a method based on postpositivism that researchers use to study the condition of natural objects, according to visible facts. Researchers collected data using observation and documentation techniques. The results of this research indicate that the cause of children experiencing speech delays at the Rumoh Terapi Tabina is the lack of time between parents and children, where children are entrusted to their caregivers so that children do not receive optimal stimulation in the form of two-way communication. communication between parents and children. Then children are given the freedom to use gadgets. Another cause is the lack of friends of the child's age in the environment where the child lives, so that the child does not have friends to communicate with.